1978
DOI: 10.3382/ps.0571075
|View full text |Cite
|
Sign up to set email alerts
|

Telemetry Measured Body Temperature of Domestic Fowl at Various Ambient Temperatures

Abstract: Adult, male Single Comb White Leghorn chickens (SCWL) were housed unrestrained in individual cages in a controlled environment room with a photoperiod of 12L:12D. By means of surgically implanted radio transmitter, body temperatures were recorded hourly for five consecutive days at each of six experimental temperatures: 23, 26, 29, 32, 35, and 38 C. The data were evaluated statistically by correlogram, periodogram, and harmonic analysis. Period length of each cycle was about 24 hr at all ambient temperatures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Also supported by USDA grant 95-37203-2702, Arkansas Agricultural Experiment Station. 2 Correspondence: Wayne L. Bacon [3][4][5][6][7][8] and Japanese quail [9,10]. Kadono and coworkers [7] found that, under conditions of constant light, chicken hens selected for increased egg production (White Leghorn) had a body temperature circadian rhythm with a period of 25.3 h that was the same as the period for ovipositions.…”
Section: Introductionmentioning
confidence: 98%
“…Also supported by USDA grant 95-37203-2702, Arkansas Agricultural Experiment Station. 2 Correspondence: Wayne L. Bacon [3][4][5][6][7][8] and Japanese quail [9,10]. Kadono and coworkers [7] found that, under conditions of constant light, chicken hens selected for increased egg production (White Leghorn) had a body temperature circadian rhythm with a period of 25.3 h that was the same as the period for ovipositions.…”
Section: Introductionmentioning
confidence: 98%
“…In studies carried out on adult roosters, Kadono and Besch (1978) showed that, among others, the rectal temperature of birds maintained at ambient temperatures (23°C) and photoperiod of 12L:12D (light during 7.00-18.00) reached a peak value (41.7-41.9°C) between 13.00-15.00, while the lowest (41.0-41.1°C) between 23.00-3.00 h. Daily temperature fluctuation equaled 0.9°C and was similar to that found in the control group of hens in our experiment.…”
Section: Osmentioning
confidence: 99%
“…Like other homeotherms, birds have developed a physical and metabolic mechanism for thermoregulation 4 . Adults chickens have an average body temperature ranging from 41 to 42 °C under thermoneutral conditions 5 . However, when the temperature rises to a certain extent, broilers’ ability to dissipate heat is markedly diminished.…”
Section: Introductionmentioning
confidence: 99%